The Multilevel and Multifaceted Character of Computer Self-Efficacy: Toward Clarification of the Construct and an Integrative Framework for Research - Marakas, George M.; Yi, Mun Y.; Johnson, Richard D. (Information Systems Research, 1998)
Despite the recent empirical interest and advances in research with regard to the construct of computer self-efficacy (CSE), the results obtained to date have, in some cases, been either equivocal or contradictory. We suggest that such results may be attributable to a general lack of attention to the dynamic, multileveled, and multifaceted nature of the computer self-efficacy construct. We offer examples from the extant CSE literature suggesting weaknesses in existing measures of the construct as well as issues associated with manipulations and the need for control of antecedent and consequent factors directly associated with CSE. The objectives of this paper are: (1) to provide a thorough review of the extant literature related to CSE; (2) to present an integrated model of empirical findings, constructed from a wide variety of disciplines, that comprehensively defines the multifaceted nature of task-specific CSE in terms of its antecedent, consequent, and moderating factors; (3) to present a conceptual model of CSE at the general versus task-specific level; and (4) to use the two models of CSE to proffer guidelines for both measurement and manipulation of the construct. Through our review of the CSE literature, we offer several thoughts regarding the nature of the empirical results obtained to date. The combined objectives serve as a basis for establishing a foundation upon which future research investigating the CSE construct can be based.